2022
DOI: 10.1038/s41598-022-11114-x
|View full text |Cite
|
Sign up to set email alerts
|

Polyhydroxyalkanoates production from short and medium chain carboxylic acids by Paracoccus homiensis

Abstract: The aim of this study was to evaluate an effect of short and medium chain carboxylic acids (CAs) rich stream derived from acidogenic mixed culture fermentation of acid whey on polyhydroxyalkanoates (PHAs) synthesis by Paracoccus homiensis and compare it with the impact of individual synthetic CAs. The obtained results confirmed that the analyzed bacterium is able to metabolize synthetic CAs as the only carbon sources in the growth medium with maximum PHAs production yields of 26% of cell dry mass (CDM). The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
1
3
1
Order By: Relevance
“…The T d for PHB produced by B. paraconglomeratum ranged from 248.6 to 258.3 °C and the T m ranged between 138 and 166 °C which was considerably higher than that of commercially synthesized biopolymers [ 34 ]. The same was observed with the PHBs of Paracoccus homiensis [ 35 ].…”
Section: Discussionsupporting
confidence: 79%
“…The T d for PHB produced by B. paraconglomeratum ranged from 248.6 to 258.3 °C and the T m ranged between 138 and 166 °C which was considerably higher than that of commercially synthesized biopolymers [ 34 ]. The same was observed with the PHBs of Paracoccus homiensis [ 35 ].…”
Section: Discussionsupporting
confidence: 79%
“…Thus, our data suggested that neither lactic acid nor ethanol affected the PHA productivity negatively. Furthermore, quite low PHA productivity was reported in the cultivation of P. homiensis grown on the same (as in our study) SMCFA extracted -rich stream, suggesting that the presence of butyric acid as the dominant component had more inhibitory effect due to the fact that a single short-chain-fatty acid in the medium resulted in the lowest PHA production efficiency compared with others (Szacherska et al, 2021).…”
Section: Resultscontrasting
confidence: 45%
“…Comparable biomass data (1.03 g/L) were reported in P. oleovorans culture supplemented with volatile fatty acid streams from chicken manure where acetate was the predominant acid ( Aremu et al, 2021 ). Higher biomass concentration was determined by our research group by supplementation of the culture medium with the same SMCFA extracted -rich stream in the cultivation of Paracoccus homiensis ( Szacherska et al, 2021 ). Moreover, our results confirmed that PHA productivity increased under nitrogen limitation, reaching a maximum value of 4.5 mg/L h at 24 h of the fermentation after ammonium exhaustion in the growth medium was reached.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large phylogenetic diversity of bacterial and archaeal species have a native PHA‐producing capability (Kim & Rhee, 1999 ; Kourilova et al, 2020 ; Mohandas et al, 2018 ; Tu et al, 2022 ; Yamane et al, 1996 ). Within the gram‐negative genus Paracoccus , several species were characterized as PHA producers, including Paracoccus pantotrophus (Ucisik‐Akkaya et al, 2009 ), Paracoccus homeinsis (Szacherska et al, 2022 ) and Paracoccus denitrificans (Yamane et al, 1996 ). The latter species has been extensively studied for its PHA‐producing capability.…”
Section: Introductionmentioning
confidence: 99%